SPK UNTUK MENENTUKAN SANKSI PESERTA DIDIK DENGAN METODE AHP DAN SAW DI SMKN 2 KURIPAN - saikin; Tuti Hardiati; Wafi’ah Murniati (Teknik: Jurnal Ilmu Teknik dan Informatika, 2022)
State Vocational High School (SMK) 2 Kuripan, is located on the border of two districts, namely West Lombok and Central Lombok with a fairly large number of students where they come from various regions with varied backgrounds and characters and it is very possible that this will happen. violations by students. Violations that often occur are indiscipline, students are late for class, truant, jumping fences, smoking, fighting and so on. For this reason, it is deemed necessary to have a system used to assist in making decisions in determining sanctions for such violations. This study aims to design a system that can help facilitate BK teachers in determining sanctions to students using the AHP (Analytic Hierarchy Process) and SAW (Simple Additive Weight) methods. In designing the system, it has several assessment criteria with weighted points and priorities for each alternative. Every violation committed by students will be processed quickly accompanied by sanctions and predetermined actions. This process can assist BK teachers in determining sanctions for students and making reports to the waka of students and the principal of SMKN 2 Kuripan.